Peran Ustadzah dalam Mengimplementasikan Pembelajaran Kitab Hidayatus Sibyan untuk Meningkatkan Kefasihan Membaca Al-Quran di Kelas I B Diniyah Putri Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan Tahun Pelajaran 2024/2025: Penelitian - Lestari, Sri; Aslamiyah, Nurul; Fauzi, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Hidayatus Sibyan book is used as a learning reference because its content is easy for students to memorize and understand. In Class 1B of the Diniyah division at Pondok Pesantren Hidayatul Mubtadiin, this book is implemented in the learning process to deepen students’ understanding of tajwid (rules of Qur’anic recitation), although several challenges are still encountered in its application. This study was conducted in Class 1B Diniyah at Pondok Pesantren Hidayatul Mubtadiin with the aim of exploring the role of the ustadzah (female Islamic teacher) in implementing the Hidayatus Sibyan learning to enhance students' fluency in reading the Qur’an. Furthermore, the study seeks to identify both the supporting and inhibiting factors in the implementation of this learning process. This research employs a qualitative approach, using data collection methods including observation, interviews, and documentation. All collected data were analyzed using a descriptive qualitative method through three main stages: data reduction, data presentation, and conclusion drawing. This process aims to provide an in-depth understanding of the ustadzah’s involvement in the teaching of the book. The results show that the ustadzah plays a fairly effective role in delivering the content of the Hidayatus Sibyan book, especially in improving students' fluency in reading the Qur’an. This is achieved through repetition techniques, memorization of verses in the book, and comprehension of their meanings. The main supporting factors identified include the ustadzah’s teaching competence, the students’ learning motivation, and the religious environment of the pesantren. Meanwhile, the inhibiting factors include limited facilities and infrastructure. Nevertheless, the learning of Hidayatus Sibyan has proven to significantly contribute to enhancing the Qur’anic reading fluency of the female students in Class 1B Diniyah